Implementation of Cyber Counseling in Higher Education Through the My Counselor Application - Hasan Bastomi; Sugiyo Sugiyo; Anwar Sutoyo; Awalya Awalya (Universitas Negeri Semarang, 2022)
Abstract. This study aims to reveal the Implementation of Cyber Counseling in Higher Education Through the My Counselor Application. Research on the Implementation of Cyber Counseling in Higher Education was conducted using a qualitative approach with the type of field research with data collection techniques using Interview, Observation and Documentation Techniques. The research subjects or informants in this research are the chairman of the My Counselor Application Founder, My Counselor Application Admin, Guidance and Counseling Students of IAIN Kudus. The results showed that there are various counseling services in the My Counselor Application, namely individual counseling, SOS Call, My Counselor Support Group, Psychological Services, Meet Counselor, Consulting Services, My Test Services.-based counseling service Self Help for My Counselor users by utilizing social media Facebook and Instagram. The research contribution in this study is about the implementation of the My Counselor Application in Counseling Services in Higher Education.